2021
DOI: 10.21037/apm-21-2563
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Compound Danshen Dripping Pills combined with western medicine in the treatment of diabetic retinopathy: a systematic review and meta-analysis of randomized controlled trials

Abstract: Background: The Compound Danshen Dripping Pills have been widely used in the treatment of DR, but there is a lack of systematic review of reports on this topic. To explore the efficacy of Compound Danshen Dripping Pills combined with western medicine in the treatment of diabetic retinopathy, we conducted a meta-analysis. Methods: Randomized controlled trials published in the Chinese Medical Literature Database (CBM), Embase, PubMed, and Medline databases from January 2010 to August 2021 were searched. After sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…CDDP is a herbal compound used for the treatment of cardiovascular diseases, made from Salvia miltiorrhiza Bunge [Lamiaceae], Panax notoginseng (Burkill) F.H.Chen [Araliaceae] and a small number of Borneolum Syntheticum, and contain active ingredients such as tanshinone, protocatechuic acid, ginsenoside, and Panax ginsenoside (62). Due to its vascular protective effects (63), CDDP is often used clinically in patients with DR. A Metaanalysis that included eight RCTs involving 524 patients found that CDDP combined with western drugs was effective in improving patients' visual function (64), which is consistent with our present NMA results. Meanwhile, basic studies have shown that CDDP can improve retinal vascular and neurological function by inhibiting inflammation, oxidative stress, and apoptosis, reducing vascular endothelial cell damage, and increasing retinal thickness (65,66), which may explain the superiority of CDDP over other OCPMs in improving visual function.…”
Section: Main Findingssupporting
confidence: 91%
“…CDDP is a herbal compound used for the treatment of cardiovascular diseases, made from Salvia miltiorrhiza Bunge [Lamiaceae], Panax notoginseng (Burkill) F.H.Chen [Araliaceae] and a small number of Borneolum Syntheticum, and contain active ingredients such as tanshinone, protocatechuic acid, ginsenoside, and Panax ginsenoside (62). Due to its vascular protective effects (63), CDDP is often used clinically in patients with DR. A Metaanalysis that included eight RCTs involving 524 patients found that CDDP combined with western drugs was effective in improving patients' visual function (64), which is consistent with our present NMA results. Meanwhile, basic studies have shown that CDDP can improve retinal vascular and neurological function by inhibiting inflammation, oxidative stress, and apoptosis, reducing vascular endothelial cell damage, and increasing retinal thickness (65,66), which may explain the superiority of CDDP over other OCPMs in improving visual function.…”
Section: Main Findingssupporting
confidence: 91%
“…Meanwhile, in long-term clinical practice, the efficacy of TCM in preventing and treating DR has been gradually recognized, and more and more scholars have tried to explore its specific mechanism of action and find high-quality evidence-based medical evidence. There are meta-analyses proving that Chinese patent medicines such as Qiming granules ( 40 ) and Fuxiang Danshin Drops ( 41 ) and so on in combination with western medical treatment can significantly improve visual acuity and fundus signs in NPDR patients; in addition, Pang B ( 42 ) In addition, Pang B’s study included 3373 subjects with NPDR and systematically evaluated the effectiveness and safety of CHCs of the blood activating and blood stasis type in the prevention and treatment of NPDR. Compared with the conventional treatment group, placebo group and blank control group, CHCs of the blood activating and blood stasis type was effective in improving patients’ BCVA, reducing microaneurysms and lowering HbA1c index, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, in long-term clinical practice, the efficacy of TCM in preventing and treating DR has been gradually recognized, and more and more scholars have tried to explore its specific mechanism of action and find high-quality evidence-based medical evidence. There are meta-analyses proving that Chinese patent medicines such as Qiming granules (40) and Fuxiang Danshin Drops (41) and so on in combination with western medical treatment can significantly improve visual acuity and fundus signs in NPDR patients; in addition, Pang B ( 42 The types and principles of CHCs are more complex than those of proprietary Chinese medicines. The CHCs summarized in this study are all empirical formulas that have been refined by various medical practitioners in their long-term clinical practice under the guidance of TCM theory and are very effective in preventing and treating early DR.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, TCM treatment of DR mainly focuses on promoting blood circulation [ 8 ]. In recent years, the combination of Chinese patent medicines (CPMs) for promoting blood circulation and CD can improve the clinical efficacy of DR [ [9] , [10] , [11] ]. Among them, Compound Danshen Dripping Pills (DS), Qiming Granule (QM), and Compound Xueshuantong Capsule (XST) have been widely used by clinicians in DR treatment.…”
Section: Introductionmentioning
confidence: 99%